2006
DOI: 10.1111/j.1365-2745.2006.01177.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Flora of the British Isles: Pteridium aquilinum (L.) Kuhn

Abstract: Summary1 This account reviews information on all aspects of the biology of bracken Pteridium (mainly aquilinum ssp. aquilinum) that are relevant to understanding its ecological characteristics and behaviour. The main topics are presented within the standard framework of the Biological Flora of the British Isles: distribution, habitat, communities, responses to biotic factors, responses to environment, structure and physiology, phenology, reproductive characters, herbivores and disease, history, and conservatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
171
1
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(207 citation statements)
references
References 239 publications
(479 reference statements)
6
171
1
13
Order By: Relevance
“…It has been evidenced that the dense understorey layer formed by bracken also increases their impact on succession by decreasing the amount of seeds reaching the soil surface and by increasing shading (Pakeman and Marrs, 1992;Marrs and Watt, 2006). This is also supported by the work of Royo and Carson (2006), who argued that the dense understorey layer in forests is one of the causes of impact on the floristic composition rather than some allelopathic effect.…”
Section: Impact Of Pteridium Fronds In the Fieldsupporting
confidence: 57%
See 2 more Smart Citations
“…It has been evidenced that the dense understorey layer formed by bracken also increases their impact on succession by decreasing the amount of seeds reaching the soil surface and by increasing shading (Pakeman and Marrs, 1992;Marrs and Watt, 2006). This is also supported by the work of Royo and Carson (2006), who argued that the dense understorey layer in forests is one of the causes of impact on the floristic composition rather than some allelopathic effect.…”
Section: Impact Of Pteridium Fronds In the Fieldsupporting
confidence: 57%
“…For woodland to develop in such a community it requires some form of disturbance leading P. aquilinum to diminish (Marrs and Watt, 2006). In Brazil, we suggest that succession does not take its natural course in the Atlantic Forest without an appropriate management of bracken, for example.…”
Section: Impact Of Pteridium Fronds In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonal plants with runners that successfully spread under later-successional vegetation stages [e.g., Brachypodium pinnatum (L.) Beauv. (de Kroon and Bobbink 1997) or Pteridium aquilinum (L.) Kuhn (Marrs and Watt 2006)] combine their clonality with biomass retention and with intact connections between ramets to continuously support new shoots, which C. dissectum does not.…”
Section: Clonal Growth Strategy Of C Dissectummentioning
confidence: 99%
“…Studies of forest ecosystems have already shown the negative impact of these three species on tree seedling establishment and growth (see e.g. Dolling, 1996;Norberg et al, 2001;Gaudio et al, 2010) and their life cycle, reproduction and resource requirements have been empirically described (for reviews, see Gimingham, 1960;Taylor et al, 2001;Marrs and Watt, 2006). They are considered light-demanding species, with Ellenberg lightrequirement indices of 6, 7 and 8 (on a scale of 9) for P. aquilinum, M. caerulea and C. vulgaris respectively (Ellenberg et al, 1992), and tolerant to acid to highly acid poor soils, and to some extent to waterlogging, which explains their broad distribution area in temperate and boreal forests.…”
Section: Introductionmentioning
confidence: 99%